2005
DOI: 10.1158/1535-7163.mct-04-0327
|View full text |Cite
|
Sign up to set email alerts
|

Murine double minute 2 as a therapeutic target for radiation sensitization of lung cancer

Abstract: Murine double minute 2 (MDM2) inhibits p53-mediated functions, which are essential for therapies using DNAdamaging agents. The purpose of this study was to determine whether MDM2 inhibition enhances the radiosensitivity of a lung cancer model. The effects of MDM2 inhibition on tumor vasculature were also studied. Transient transfection of H460 lung cancer cells and human umbilical vascular endothelial cells (HUVEC) with antisense oligonucleotides (ASODN) against MDM2 resulted in a reduced level of MDM2 and inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
2
6
0
Order By: Relevance
“…The present study is the first to look at the effects of nutlin on normal endothelial cells, which is p53 competent, and how nutlin 3a effects on vascular endothelium may be augmented by radiation. This is consistent with our study using antisense approach (42). MDM2 inhibition may have antiangiogenic effects because of its induction of p53 expression, which has been shown to induce the expression of angiogenesis inhibitors, such as thrombospondin-1, and to decrease the expression of vascular endothelial growth factor (43 -47).…”
Section: Discussionsupporting
confidence: 91%
“…The present study is the first to look at the effects of nutlin on normal endothelial cells, which is p53 competent, and how nutlin 3a effects on vascular endothelium may be augmented by radiation. This is consistent with our study using antisense approach (42). MDM2 inhibition may have antiangiogenic effects because of its induction of p53 expression, which has been shown to induce the expression of angiogenesis inhibitors, such as thrombospondin-1, and to decrease the expression of vascular endothelial growth factor (43 -47).…”
Section: Discussionsupporting
confidence: 91%
“…The activity of Mdm2 to negatively regulate p53 suggests a role of Mdm2 in modifying the resistance of tumor cells to p53-mediated cell death induced by stimuli such as ionizing radiation and hyperthermia. Consistently, it has been reported that decreased levels of Mdm2 sensitize tumor cells to ionizing radiation (Perry 2004, Cao et al 2005.…”
Section: Introductionsupporting
confidence: 61%
“…However, an experimental study demonstrated that the inhibition of MDM2 using antisense oligonucleotides increased the expression of p53 and p21 and decreased the survival of lung cancer cells following irradiation [56]. This result suggested the possibility of MDM2 being a therapeutic target for radiation sensitization against lung cancer.…”
Section: Mdm2 In Nsclcsmentioning
confidence: 99%